Bearwalker - Bruchac, Joseph, 1942- (Harper, 2010)
Although the littlest student in his class, thirteen-year-old Baron Braun calls upon the strength and wisdom of his Mohawk ancestors to face both man and beast when he tries to get help for his classmates, who are being terrorized during a school field trip in the Adirondacks.